2019
DOI: 10.7717/peerj.6961
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations of microbial communities in abyssal and hadal sediments across the Challenger Deep

Abstract: Microbial communities in hadal sediments are least explored in hadal zone (>6,000 m), especially in the Challenger Deep with high pressure (∼110 M pa at the bottom). In this study, we investigated the microbial communities in the sediments of the slope and trench-axis bottom of the Challenger Deep in the Mariana Trench. Classification of the reads of the 16S rRNA gene amplicons showed vertical distribution of prokaryotic microbial inhabitants from the surface to up to 60 centimeter below surface floor (cmbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 56 publications
12
35
0
Order By: Relevance
“…Conversely, Proteobacteria and Thaumarchaeota dominated in shallower sections. These trends are similar to previous studies [20, 21, 48, 5456]. and likely depend on the concentrations of dissolved oxygen and nitrate in sediments.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Conversely, Proteobacteria and Thaumarchaeota dominated in shallower sections. These trends are similar to previous studies [20, 21, 48, 5456]. and likely depend on the concentrations of dissolved oxygen and nitrate in sediments.…”
Section: Resultssupporting
confidence: 91%
“…S8). In general, the dominant phyla were similar to those of previous studies of abyssal and hadal sediments [20, 21, 48, 5456].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Our results showed that sediment and water microbial betadiversity was significantly different among vulnerable, endemic, and epidemic SCTLD zones (Figure 3). Water and sediments collected from distinct geographical regions can have discrete microbial compositions (Cui et al, 2019;Glasl et al, 2019). Although geographical location may have been the main factor driving site groupings (Glasl et al, 2019), this pattern is intertwined with the unique environmental conditions from FIGURE 10 | Rhizobiales and Rhodobacterales found in sediment and water samples that were significantly differentiated in diseased colony lesions.…”
Section: Potential Microbial Signatures Associated With Sctld Outbreamentioning
confidence: 99%
“…Therefore, the labile organic carbon deposition in hadal zone supported by the high sedimentation is considered to facilitate establishment of distinct faunal and prokaryotic community observed at global scales [15][16][17][18][19]. Recently, the influence of physicochemical features on hadal biospheres were reported for microbial communities in the Mariana and Kermadec Trench regions [20,21], where under oligotrophic and relatively eutrophic (intermediate) ocean, respectively [22,23]; the pioneering studies reported microbial biodiversity in hadal trench bottom, trench slope, and adjusted abyssal plain sediments using culture-independent highthroughput sequencing techniques, and consequently demonstrated the structural similarity among each abyssal and hadal site. However, relations between geochemistry and microbial composition in hadal trench bottom and adjacent abyssal sediments have been still uninvestigated.…”
Section: Introductionmentioning
confidence: 99%